METHODOLOGY FOR TEACHING THE SUBJECT OF HISTORICAL GEOGRAPHY USING MODERN PEDAGOGICAL TECHNOLOGIES - Rizomat Adashvoyevich Karimov (Bright Mind Publishing, 2025)
This study explores the methodology for teaching the subject of historical geography using modern pedagogical technologies. The research focuses on how interactive learning platforms, multimedia resources, virtual field trips, and simulations can enhance the learning experience and foster critical thinking, creativity, communication, and collaboration skills in students. The study involves 100 high school students divided into two groups: an experimental group, which receives instruction using modern technologies, and a control group, which is taught using traditional methods. The findings suggest that integrating multimedia and interactive tools significantly improves student engagement, understanding of historical-geographical concepts, and the development of essential 21st-century skills. This paper demonstrates that modern pedagogical technologies not only enhance students' academic performance but also better prepare them for the challenges of the future by encouraging active participation and fostering deeper learning.
Keywords: Historical geography, pedagogical technologies, modern education, interactive learning, multimedia resources, virtual field trips, 21st century skills, critical thinking, creativity, collaboration, education innovation.